(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article analyzes the state and development of human resource management technologies in the pharmaceutical field, describes the main strategic and tactical functions of human resource management, analyzes the evolution of human resource management, and describes information systems for human resource management.